2021
DOI: 10.1002/nop2.1139
|View full text |Cite
|
Sign up to set email alerts
|

Clinical placements as a challenging opportunity in midwifery education: A qualitative study

Abstract: Aim The aim of this qualitative study was to explore some of the existing statuses of clinical education and examine the strengths and weaknesses of the clinical faculty programme. Design A qualitative study. Methods This qualitative study was designed through the directed content analysis approach, which was completed according to the Context, Input, Process, and Product evaluation model. The purposeful sampling method of maximum variation was employed to select 33 participants, and the data were collected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…PROSPERO Registration Number is, CRD42022369713 in 01.11.2022 Background One of the most important strategies for preparing students to enter the clinical environment, accept responsibility, and improve their ability to make health decisions is clinical education (1). Studies have shown that medical students, especially midwives and nurses, as the front line of treatment, face some di culty in learning clinical skills to reach a level of competence and safe performance in clinical environments (2,3,4,5).…”
Section: Systematic Review Registrationmentioning
confidence: 99%
“…PROSPERO Registration Number is, CRD42022369713 in 01.11.2022 Background One of the most important strategies for preparing students to enter the clinical environment, accept responsibility, and improve their ability to make health decisions is clinical education (1). Studies have shown that medical students, especially midwives and nurses, as the front line of treatment, face some di culty in learning clinical skills to reach a level of competence and safe performance in clinical environments (2,3,4,5).…”
Section: Systematic Review Registrationmentioning
confidence: 99%
“…( Davis et al., 2018 ; Marzalik, Feltham, Jefferson, & Pekin, 2018 ; Panda, Dash, & John, 2021 ) Limited clinical opportunities during training can create competency gaps for newly-graduated nurses. ( Michel, Ryan, & Mattheus, 2021 ; Modarres, Geranmayeh, Amini, & Toosi, 2022 ; Ochylski, Aebersold, & Kuebric, 2017 ) An increasing number of schools worldwide are turning to simulation to increase opportunities for hands-on experiences. ( Fuglsang, Bloch, & Selberg, 2022 ; Mulyadi, Tonapa, Rompas, Wang, & Lee, 2021 )…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of China's foreign trade needs a large number of business talents with comprehensive qualities. Business English has not only become a "bridge" for China's foreign economy, but also an important means of cultural exchange [2]. In order to fill the "gap" in the social demand for business English professionals, there are more than 800 colleges and universities offering business English courses in China, which basically meet the demand of foreign trade in China for English professionals [3].…”
Section: Introductionmentioning
confidence: 99%